Increased production of orthoflavivirus single-round infectious particles produced in mammalian cells at a suboptimal culture temperature of 28°C - Tabata, Koshiro; Kobayashi, Shintaro; Itakura, Yukari; Gonzalez, Gabriel; Kabamba, Chilekwa F.; Saito, Shinji; Sasaki, Michihito; Hall, William W.; Sawa, Hirofumi; Orba, Yasuko (Journal of virological methods, 2024)
In the employment of serodiagnostic methods for the detection of orthoflavivirus infections, neutralization tests are known to be more accurate than measurements of antibody binding properties employing enzyme-linked immunosorbent assays. However, neutralization tests require infectious virus and laboratories with an appropriate level of biosafety. Single-round infectious particles (SRIPs), which encode a reporter gene instead of the viral structural protein genes, are replication incompetent and represent a safe and reliable alternative to the diagnosis of pathogenic viruses in neutralization tests. The orthoflavivirus SRIPs are produced by co-transfection of plasmids expressing virus-like particles and replicons into mammalian cell lines preferably with high transfection efficacy, such as HEK293T cells. However, certain orthoflavivirus SRIPs have limitations in their efficient expression at 37°C, which is the optimal temperature for mammalian cell growth, resulting in insufficient yields for neutralization tests. Here, we demonstrate that the production of orthoflavivirus SRIPs increases at the lower temperature of 28°C compared to 37°C. Moreover, infections with 28°C-cultured SRIPs in microneutralization tests were specifically inhibited in the presence of serum from mice infected with homologous viruses, suggesting that these SRIPs preserved their neutralizing epitopes for antibodies. Our method to produce high titer SRIPs is anticipated to promote efficient and safe SRIPs neutralization tests as a general serodiagnostic method for detecting virus-specific neutralizing antibodies against orthoflaviviruses.